2020
DOI: 10.1038/s41598-020-62799-x
|View full text |Cite
|
Sign up to set email alerts
|

Axial stretch regulates rat tail collecting lymphatic vessel contractions

Abstract: Lymphatic contractions play a fundamental role in maintaining tissue and organ homeostasis. The lymphatic system relies on orchestrated contraction of collecting lymphatic vessels, via lymphatic muscle cells and one-way valves, to transport lymph from the interstitial space back to the great veins, against an adverse pressure gradient. Circumferential stretch is known to regulate contractile function in collecting lymphatic vessels; however, less is known about the role of axial stretch in regulating contracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
3
11
0
Order By: Relevance
“…The estimated parameters for the axial and diagonal collagen fibres implies the axial fibre family plays a significant role in the load-bearing function. The significance of axial stretch in passive behaviour of lymphatic vessels is in agreement with our recent quantification of collagen fibre orientation in the rat tail lymphatic, where the vessels have a predominant organization of collagen fibres in the axial direction and experience axial prestretch of approximately 20% in situ [9]. Non-parametric bootstrapping, used to assess the uniqueness of the fitted parameter sets and to obtain the confidence intervals of estimated parameters, showed that the three-fibre family model yielded a unique set of material parameters.…”
Section: Robust Three-fibre Family Model Fit Experimental Data Well and Yielded Unique Parameter Setssupporting
confidence: 90%
See 4 more Smart Citations
“…The estimated parameters for the axial and diagonal collagen fibres implies the axial fibre family plays a significant role in the load-bearing function. The significance of axial stretch in passive behaviour of lymphatic vessels is in agreement with our recent quantification of collagen fibre orientation in the rat tail lymphatic, where the vessels have a predominant organization of collagen fibres in the axial direction and experience axial prestretch of approximately 20% in situ [9]. Non-parametric bootstrapping, used to assess the uniqueness of the fitted parameter sets and to obtain the confidence intervals of estimated parameters, showed that the three-fibre family model yielded a unique set of material parameters.…”
Section: Robust Three-fibre Family Model Fit Experimental Data Well and Yielded Unique Parameter Setssupporting
confidence: 90%
“…The three-fibre family constitutive model yielded a good fit (R 2 = 0.90 ± 0.03) for the rat tail lymphatic vessels (figure 1 and table 1, using the geometric parameters in table 2). Supporting the previous experimental observation, our modelling results indicate that a three-fibre family model was sufficient to provide a good fit of biaxial data [9]. Based on the estimated parameters, the axial fibre family and two symmetric diagonal fibre families significantly contribute to the load-bearing function of lymphatic vessels; however, the isotropic term (namely, c(I C À 3)) had a much smaller contribution; i.e.…”
Section: Passive and Active Biomechanical Propertiessupporting
confidence: 83%
See 3 more Smart Citations